Frequency of Red Blood Cell Antigens According to Parent Ethnicity in Korea Using Molecular Typing - Shin, Kyung Hwa; Lee, Hyun Ji; Kim, Hyung Hoi; Hong, Yun Ji; Park, Kyoung Un; Kim, Min Ju; Kwon, Jeong Ran; Choi, Young Sil; Kim, Jun Nyun (Annals of laboratory medicine, 2018)
Frequencies of red blood cell (RBC) blood group antigens differ by ethnicity. Since the number of immigrants is increasing in Korea, RBC antigens should be assessed in children/youths with parents of different ethnicities to ensure safe transfusions. We investigated the frequency of RBC antigens, except for ABO and RhD, in 382 children and youths with parents having Korean and non-Korean ethnicities. Subjects were divided into those with ethnically Korean parents (Korean group; N=252) and those with at least one parent of non-Korean ethnicity (non-Korean group; N=130). The 37 RBC antigens were genotyped using the ID CORE XT system (Progenika Biopharma-Grifols, Bizkaia, Spain). The frequencies of the Rh (E, C, e, hr(S), and hr(B)), Duffy (Fy(a)), MNS (Mi(a)), and Cartwright (Yt(b)) antigens differed significantly between the two groups. Eight and 11 subjects in the Korean and non-Korean groups, respectively, exhibited negative expression of high-frequency antigens, whereas 14 subjects in the non-Korean group showed positive expression of low-frequency antigens. The frequency of RBC antigens has altered alongside demographic changes in Korea and might lead to changes in distribution of RBC antibodies that cause acute or delayed hemolytic transfusion reaction.